A Novel Cellular Handset Design for an Enhanced Antenna Performance and a Reduced SAR in the Human Head - Salah I. Al-Mously; Marai M. Abousetta (International Journal of Antennas and Propagation)
This paper presents a novel cellular handset design with a bottom-mounted short loaded-whip antenna. This new handset design is modeled and simulated using a finite difference time-domain (FDTD)-based platform SEMCAD. The proposed handset is based on a current commercially available bar-phone type with a curvature shape, keypad positioned above the screen, and top-mounted antenna. The specific absorption rates (SARs) are determined computationally in the specific anthropomorphic mannequin (SAM) and anatomically correct model of a human head when exposed to the EM-field radiation of the proposed cellular handset and the handset with top-mounted antenna. The two cellular handsets are simulated to operate at both GSM standards, 900 MHz as well as 1800 MHz, having different antenna dimensions and intput power of 0.6 W and 0.125 W, respectively. The proposed human hand holding the two handset models is a semirealistic hand model consists of three tissues: skin, muscle, and bone. The simulations are conducted with handset positions based on the IEEE standard 1528-2003. The results show that the proposed handset has a significant improvement of antenna efficiency when it is hand-held close to head, as compared with the handset of top-mounted antenna. Also, the results show that a significant reduction of the induced SAR in the human head-tissues can be achieved with the proposed handset.